1999
DOI: 10.1017/s0043174500091608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage and crop residue on postdispersal predation of weed seeds

Abstract: Field experiments were conducted from 1995 to 1997 in southern Ontario to determine the influence of tillage and ground cover on the quantity of postdispersal seed predation of common lambsquarters and barnyardgrass. Ground-dwelling invertebrates were the dominant seed predators and were responsible for 80 to 90% of all seeds consumed. Predation was highest in no-till and moldboard-plowed environments (averaging 32% in both) and lowest in chisel-plowed environments (averaging 24%). This indicates that the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
160
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 48 publications
6
160
2
Order By: Relevance
“…Other studies have found no difference (Cardina et al, 1996;Cromar et al, 1999), but both of these studies were conducted in plots less than 0.3 ha in size which may not have been large enough to detect differences due to the mobility of predators . The reported increases in numbers of predators may be due to both increased habitat (Díaz, 1991;Kromp, 1999;Cunningham et al, 2004;Baraibar et al, 2009) or decreased tillage-induced mortality (Thorbek and Bilde, 2004;Shearin et al, 2007).…”
Section: Predation Of Weed Seedsmentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies have found no difference (Cardina et al, 1996;Cromar et al, 1999), but both of these studies were conducted in plots less than 0.3 ha in size which may not have been large enough to detect differences due to the mobility of predators . The reported increases in numbers of predators may be due to both increased habitat (Díaz, 1991;Kromp, 1999;Cunningham et al, 2004;Baraibar et al, 2009) or decreased tillage-induced mortality (Thorbek and Bilde, 2004;Shearin et al, 2007).…”
Section: Predation Of Weed Seedsmentioning
confidence: 88%
“…Studies have shown residue effects on predation rates depend on the type of residue, surrounding landscapes, and the type of native predator populations (Bommarco, 1998;Cromar et al, 1999;Liebman, 2001). Some studies report extended season ground cover is correlated with increased predation (Gallandt et al, 2005;Heggenstaller et al, 2006) while others have found no effect (Harrison et al, 2003;Jacob et al, 2006;Chauhan et al, 2010).…”
Section: Weed Seed Predation Pathogen Attack and Viabilitymentioning
confidence: 99%
“…Although the no-till type seems best suited to expose weed seeds at the soil surface and sustain predator populations (Brust and House, 1988;Harrison et al, 2003), Cardina et al (1996) and Cromar et al (1999) did not find different predation rates in mouldboardploughed and no-till crop fields. Mice, beetles and birds may consume large amounts of weed seeds, but the amounts vary with species, time and space (Lutman et al, 2002;Harrison et al, 2003;Westerman et al, 2003).…”
Section: No-till Management Unitsmentioning
confidence: 83%
“…The predation might occur either pre-dispersal while the seeds were still attached with the weed plants or post dispersal ("choke point" period in the weed life cycle), a form of biological means of keeping weeds under check could contribute significantly to weed population regulation (Ward et al, 2011) under NT. Nonlinear relationship between the level of disturbance and predation was observed and the predation of common lambsquarters and barnyardgrass was highest in NT (32%) at southern Ontario. Predation inclination of crop residues in NT viz., corn residue, soybean, and wheat were akin to the other (Cromar et al, 1999). Baraibar et al (2009) also found that NT increased seed predation in cereal production.…”
Section: Weed Seed Predationmentioning
confidence: 92%
“…Ground-dwelling invertebrates (Shearin et al, 2007) were the dominant seed predators and were responsible for 80-90% of common lambsquarters and barnyardgrass seeds consumed at southern Ontario (Cromar et al, 1999) and these beetle banks contribute to conservation of biodiversity in agroecosystems (MacLeod et al, 2004). Bohan et al (2011) have found that carabids can elicit regulatory effects on moncotyledon and total weed seedbanks from fields undergoing management by farmers.…”
Section: Carabidsmentioning
confidence: 99%